Hybrid Photothermal Pyroelectric and Thermogalvanic Generator for Multisituation Low Grade Heat Harvesting. Issue 33 (14th October 2018) - Ding, Tianpeng; Zhu, Liangliang; Wang, Xiao‐Qiao; Chan, Kwok Hoe; Lu, Xin; Cheng, Yin; Ho, Ghim Wei
Abstract: Harvesting of prevalent low grade solar heat from otherwise wasted energy has received tremendous attention. However, extensive and continuous conversion remains challenging due to distributed nature of heat, limited temperature difference with the surroundings, ambient solar heat fluctuation, and night time period of darkness. Herein, a hybrid thermogalvanic and pyroelectric generator for multisituation structured/unstructured, static/dynamic, and day/night waste heat harnessing for continuous operation is reported. Powered by versatile thermal energy harvesting strategies, the hybrid photothermal generator is able to provide a more resilient and adaptive energy system to meet diversified energy demand, irrespective of unpredictable conditions. Taking advantage of the superior photothermal properties and electrical conductivity of carbon nanotubes/cellulose nanocrystals nanocomposite, together with the heat localization effect induced by sponge‐confined electrolyte, simultaneous high thermogalvanic and pyroelectric performance is achieved with maximum outputs of 1.86 and 0.9 mW m −2, respectively. Moreover, a scaled‐up hybrid photothermal generator is successfully deployed on both land and water surfaces under natural sunlight, and also the feasibility of nighttime operation is verified. Such hybrid photothermal generators presented here offer an all‐day clean energy solution as well as a feasible and cost‐effective alternative to capitalize on solar energy and blue energy. Abstract : A hybrid photothermal generator consisting of a thermocell and a pyroelectric generator performs multisituation waste heat harvesting for continuous operation irrespective of unpredictable conditions and day/night alteration.